Differences in fungal communities in the fur of two- and three-toed sloths revealed by ITS metabarcoding - Rojas Gätjens, Diego (2023)
Sloths have dense fur on which insects, algae, bacteria and fungi coexist. Previous studies using cultivation-dependent methods and 18S rRNA sequencing revealed that the fungal communities in their furs comprise members of the phyla Ascomycota and Basidiomycota. In this note, we increase the resolution and knowledge of the mycobiome inhabiting the fur of the two- (Choloepus hoffmanni) and three-toed (Bradypus variegatus) sloths. Targeted amplicon metagenomic analysis of ITS2 nrDNA sequences obtained from 10 individuals of each species inhabiting the same site revealed significant differences in the structure of their fungal communities and also in the alpha-diversity estimators. The results suggest a specialization by host species and that the host effect is stronger than that of sex, age and animal weight. Capnodiales were the dominant order in sloths’ fur and Cladosporium and Neodevriesia were the most abundant genera in Bradypus and Choloepus, respectively. The fungal communities suggest that the green algae that inhabit the fur of sloths possibly live lichenized with Ascomycota fungal species. The data shown in this note offer a more detailed view of the fungal content in the fur of these extraordinary animals and could help explain other mutualistic relationships in this complex ecosystem.